RECONCILING INUIT ELDERS’ LONG-TERM CARE NEEDS: EARTH-SKY VERTEBRAL SPINES AND UMBILICAL CORDS (Canadian Journal of Native Studies, 2026)
Inuit Elders who have chronic health needs are removed and relocated todistant non-Inuit communities and institutions for long-term palliative andhospice care. There is an obvious systemic problem where governmentswith limited funding, in harsh and complex environs, are unable toprovide the requisite health care, housing, and other social services andinfrastructure that Inuit communities and people direly need. This essayseeks to describe the tragic irony the system of Inuit Elder long-termresidential care represents. Reminiscent of Residential Schools, Inuitonly can best judge how well they have progressed or achieved theirgoals of self-determination and self-governance.